Ketidakadilan dalam Puisi “Tanah Air Mata” Karya Sutardji Calzoum Bahri - Yuni Susilowati; Hidayah Budi Qur’ani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2021)
Poetry is a literary work that is often used to describe environmental conditions and the condition of the author himself. The depiction is expressed and packaged in poetry with a very deep selection of diction and meaning. The poem “Tanah Air Mata” by Sutardji Calzoum Bahri describes the condition of the Riau area that has occurred injustice between the government and the local community. The researcher raises the problem formulation, What are the forms of injustice in the poem “Tanah Air Mata” by Sutardji Colzoum Bahri ?. The purpose of this research is to find out the forms of injustice contained in the poem